Green synthesis of Piper chaudocanum stem extract mediated silver nanoparticles for colorimetric detection of Hg2+ ions and antibacterial activity. Issue 2 (8th February 2023) - Tam, Khieu Thi; Thuy, Nguyen Thi; Ngan, Nguyen Thi Kim; Khai, Nguyen Manh; Van Thanh, Dang
Abstract : A green synthetic approach to synthesize silver nanoparticles (AgNPs) using the stem extract of Piper chaudocanum for highly sensitive colorimetric detection of Hg 2+ with a low limit of detection of 23 nM and easy colorimetric read-out has been reported. In addition, the biosynthesized AgNPs demonstrated efficient antibacterial activity against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus . The morphology and structure of the as-synthesized AgNPs were examined using SEM, TEM, EDX, XRD and FT-IR analyses. The XRD and TEM results confirm the formation of AgNPs with an average particle size of 8–12 nm. The TLC, CC and HPLC revealed that four main compounds, pentacosanoic acid (1 ), piperine (2 ), β -sitosterol (3 ), and campesterol glucoside (4 ), isolated from P. chaudocanum extract act as reducing and stabilizing agents for AgNP formation, and piperine plays a vital role in green synthesis. The chemical structures of these compounds were determined by ESI MS, FTIR, and one- and two-dimensional NMR spectroscopic data analysis. This approach is an efficient, green, cost-effective, eco-friendly and promising technique for synthesizing AgNPs with applications in the colorimetric detection of Hg 2+ and antibacterial activity.